(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the clinical features and evaluate the surgical outcomes of hypospadias surgery at Nghe An Obstetrics and Pediatrics Hospital. Methods: A retrospective descriptive study of 48 patients with hypospadias who underwent surgery at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to August 2023. Results: The mean age was 5.67 years (ranging from 2 to 13 years). Thirty-nine patients (81.25%) required curvature correction procedures, including Baskin and Nesbit techniques. The average surgery time was 156.67 ± 30.06 minutes. Common postoperative complications included edema (60.42%), urine leakage around the catheter (31.25%), and catheter dislodgement (20.83%). Post-discharge follow-up results showed that the rates of urethrocutaneous fistula and urethral stricture were 16.67% and 2.08%, respectively. Early complications during the postoperative period significantly related to urethrocutaneous fistula included infection (24.13%) and urine leakage around the catheter (40%). The success rate based on the HOSE score was 93.75% at discharge and 91.67% at follow-up. Conclusion: Hypospadias surgery at Nghe An Obstetrics and Pediatrics Hospital shows promising results with a low overall complication rate.